2019
DOI: 10.1186/s12974-019-1592-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (COX-2) inhibitors: future therapeutic strategies for epilepsy management

Abstract: Epilepsy, a common multifactorial neurological disease, affects about 69 million people worldwide constituting nearly 1% of the world population. Despite decades of extensive research on understanding its underlying mechanism and developing the pharmacological treatment, very little is known about the biological alterations leading to epileptogenesis. Due to this gap, the currently available antiepileptic drug therapy is symptomatic in nature and is ineffective in 30% of the cases. Mounting evidences revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 161 publications
(168 reference statements)
3
91
0
Order By: Relevance
“…In this view, a significant attempt has been made to ameliorate the seizure induction via the implementation of selective COX-2 inhibitors such as celecoxib or aspirin. 8 The result of the present investigation also suggests that the administration of P. amarus attenuated PTZ-induced convulsion and kindling via inhibition of COX-2 and TLR-4 expressions, which is line with findings of the previous researcher. 17 Management of epileptogenesis with the use of herbal therapies provide a ray of hope due to its less side effect as compared to existing antiepileptic drugs (AEDs).…”
Section: Discussionsupporting
confidence: 92%
“…In this view, a significant attempt has been made to ameliorate the seizure induction via the implementation of selective COX-2 inhibitors such as celecoxib or aspirin. 8 The result of the present investigation also suggests that the administration of P. amarus attenuated PTZ-induced convulsion and kindling via inhibition of COX-2 and TLR-4 expressions, which is line with findings of the previous researcher. 17 Management of epileptogenesis with the use of herbal therapies provide a ray of hope due to its less side effect as compared to existing antiepileptic drugs (AEDs).…”
Section: Discussionsupporting
confidence: 92%
“…More than twenty-five cytokines are controlled directly by NF-κB. On the other hand, high levels of TNF-α promptly activates Cox-2 and NF-κB in a positive feedback loop (37). In a study of Walker et al (38) celecoxib has shown a similar Cox-2 selectivity ratio to diclofenac.…”
Section: Discussionmentioning
confidence: 99%
“…More than twenty-ve cytokines are controlled directly by NF-κB. On the other hand, high levels of TNF-α promptly activates Cox-2 and NF-κB in a positive feedback loop (43). In a study of Walker et al (44) celecoxib has shown a similar Cox-2 selectivity ratio to diclofenac.…”
Section: Discussionmentioning
confidence: 99%